Advancing the allostatic load model in military training research: from theory to application - Feigel, Evan D.; Koltun, Kristen J.; Lovalekar, Mita; Friedl, Karl E.; Martin, Brian J.; Nindl, Bradley C. (Frontiers in Physiology, 2025)
Research physiologists use theoretical models to test new empirical relationships between physiological variables and psycho-physiological outcomes and compare observed outcomes with theoretical predictions to support or refute models. Models, while valuable, often focus on a limited perspective as part of a larger reality. In understanding Warfighter health, a more holistic perspective within a model is needed since this population is exposed to a high degree of physical, cognitive, and emotional demands/loads during training throughout a career. Focusing on the physical performance aspects of occupational exposures is important; however, this neglects imperative interrelationships between the psychological and musculoskeletal domains of health, which must be quantified for early in-field prevention of injury, underperformance, or psychological harm. Chronic duration of the physiological stress response may disrupt adaptive mechanisms and result in allostatic load, characterized as a maladaptive biological process by which physiological stability (‘allostasis’) fails owing to repeated and chronic stress exposure, which can negatively affect physical and cognitive function. It may also increase vulnerability to atypical reductions in occupational physical performance and psychological and musculoskeletal health. The purpose of this review was to (i) summarize empirical research of atypical, negative consequences of military training on physical performance and psychological and musculoskeletal health (ii); reconsider the underlying biological process rendering maladaptive outcomes observed during training by leveraging a ‘stress perspective’ wherein military training-related stressors perturb stress systems and lead to allostatic load, which may serve as a mechanism by which maladaptation occurs; (iii) summarize the impact of allostatic load quantified by the Allostatic Load Index (ALI) on physical performance, psychological wellbeing, and musculoskeletal health; and (iv) propose the use of valid and reliable commercially-available wearable devices as tools to measure allostatic load by collecting longitudinal cardiometabolic and neurobehavioral (sleep) data during training and determining verifiable signals associated with ALI and maladaptive outcomes. Allostatic load is an evolving model that may be suited to understand the long-term health effects of military training-related stress. There is opportunity to improve our understanding of measurement tools involving wearables to establishing the relationship between allostatic load and long-term health outcomes in military personnel.